The role of negative affect in the persistence of nicotine dependence among alternative high school students: A latent growth curve analysis. (1st April 2020) - Miller, Stephen; Pike, James; Shono, Yusuke; Beleva, Yuliyana; Xie, Bin; Stacy, Alan W
Highlights: Negative affect is a significant risk factor for nicotine dependence. There is evidence that negative affect may predict continued dependence on nicotine. Addressing negative affect during adolescence may be critical to preventing lifelong nicotine dependence. Abstract: Background: Previous research has demonstrated how negative affect (i.e., depression, anxiety, stress) is often a correlate of and precursor to nicotine dependence. Although recent evidence shows a gradual decline in tobacco use in the United States, subgroups that report higher levels of negative affect may continue to be at risk of becoming dependent on nicotine. One high-risk subgroup is students who attend alternative high schools. The current longitudinal investigation examined the effect of negative affect on nicotine dependence in this youth population. Methods: 1060 students from 29 alternative high schools in Southern California completed a series of attitudinal and behavioral measures once per year over a three-year period. The main outcome was nicotine dependence i.e., feeling a strong urge to use nicotine products or experiencing withdrawal symptoms after a period of abstinence, measured using a version of the Fagerstrom Tolerance Questionnaire designed for adolescents. A latent growth curve model was utilized to examine the effect of negative affect on nicotine dependence during this timeframe. Results: The analysis revealed that negative affect had both a concurrent and prospective relationship with nicotine dependence. Moreover, the association between negative affect and nicotine dependence in the present was not statistically significant once the influence of negative affect reported one year earlier was accounted for. Conclusions: Negative affect may play a critical role in the persistence of nicotine dependence among high-risk youth. Providing resources to help manage negative affect may be critical to curtailing nicotine dependence in this population.